IMPROVING THE METHODOLOGY OF PRODUCT COST FORMATION IN CARPET MANUFACTURING ENTERPRISES - Teshaboyeva Mohigul Eldorjon qizi (Research Focus International Scientific Journal, 2025)
this paper examines the principles of cost formation in the carpet manufacturing industry, focusing on strategies to enhance cost calculation methods in production enterprises. It highlights the importance of accurate cost classification, the impact of cost price on competitiveness, and the role of digital technologies in expense management. Using Evaks Fabric LLC as a case study, the research analyzes how production costs are tracked, calculated, and optimized. It also outlines government policies aimed at supporting carpet manufacturing in Uzbekistan, along with practical solutions to reduce production costs and improve profitability.